Introducing a Clinical Summary Template From the Adult Day Center to Support Decision Making by Primary Care Providers - Jie Zhong; Jonelle Boafo; Tina R. Sadarangani (SAGE Publishing, 2022)
Introduction: CareMOBI (Mhealth for Organizations to Bolster Interconnectedness) is a mobile application designed to facilitate information exchange between primary care providers (PCPs) and adult day centers (ADCs). A key function of CareMOBI is to synthesize information collected outside of the provider's office (ie,: in the ADC or at home) and distill the most relevant data points into an exportable clinical summary that can help inform clinical decision making by the PCP with information from outside providers who are not formally embedded within health systems. In this study, we used a qualitative approach to understand the acceptability and utility of the clinical summary template within CareMOBI. Methods: Purposive sampling, followed by snowball sampling, was used to recruit PCPs from a variety of primary care practice settings (i.e. home-based, academic). Semi-structured interviews were conducted virtually to elicit feedback on the user-experience after interaction with a prototype template. Interviews were recorded, transcribed, and analyzed using content analysis. Results: Our sample (n = 10) consisted of physicians and nurse practitioners in a variety of settings. Feedback suggested that the summary template facilitates interdisciplinary, bidirectional, succinct, and relevant information exchange across care teams. The summary template effectively integrates observations and assessments from team members, centralizes them, and allows PCPs to hone in on the most salient components to inform clinical decision making for the geriatric patient. The summary gave PCPs "live texture" about what was happening outside the office and represented a significant improvement over other methodologies of information exchange. Prior to implementation into clinical practice, several refinements are necessary based on feedback including integration into the PCP's workflow. Conclusions: The template was viewed by PCPs as a concise and actionable record, in contrast to current communication which is characterized as "bloated"-containing too many pages on nonessential information. The summary could potentially save PCP's time in locating and analyzing historical data to enable rapid patient assessment and prompt more ready and informed action.